Phasevarion mediated epigenetic gene regulation in Helicobacter pylori. - Yogitha N Srikhanta (Public Library of Science (PLoS), 2011)
Many host-adapted bacterial pathogens contain DNA methyltransferases (mod genes) that are subject to phase-variable expression (high-frequency reversible ON/OFF switching of gene expression). In Haemophilus influenzae and pathogenic Neisseria, the random switching of the modA gene, associated with a phase-variable type III restriction modification (R-M) system, controls expression of a phase-variable regulon of genes (a "phasevarion"), via differential methylation of the genome in the modA ON and OFF states. Phase-variable type III R-M systems are also found in Helicobacter pylori, suggesting that phasevarions may also exist in this key human pathogen. Phylogenetic studies on the phase-variable type III modH gene revealed that there are 17 distinct alleles in H. pylori, which differ only in their DNA recognition domain. One of the most commonly found alleles was modH5 (16% of isolates). Microarray analysis comparing the wild-type P12modH5 ON strain to a P12ΔmodH5 mutant revealed that six genes were either up- or down-regulated, and some were virulence-associated. These included flaA, which encodes a flagella protein important in motility and hopG, an outer membrane protein essential for colonization and associated with gastric cancer. This study provides the first evidence of this epigenetic mechanism of gene expression in H. pylori. Characterisation of H. pylori modH phasevarions to define stable immunological targets will be essential for vaccine development and may also contribute to understanding H. pylori pathogenesis.